Tethering Luminescent Thermometry and Plasmonics: Light Manipulation to Assess Real-Time Thermal Flow in Nanoarchitectures - Brites, Carlos D. S. (2017)
The past decade has seen significant progresses in the ability to fabricate new mesoporous thin films with highly controlled pore systems and emerging applications in sensing, electrical and thermal isolation, microfluidics, solar cells engineering, energy storage, and catalysis. Heat management at the micro- and nanoscale is a key issue in most of these applications, requiring a complete thermal characterization of the films that is commonly performed using electrical methods. Here, plasmonic-induced heating (through Au NPs) is combined with Tb3+/Eu3+ luminescence thermometry to measure the thermal conductivity of silica and titania mesoporous nanolayers. This innovative method yields values in accord with those measured by the evasive and destructive conventional 3Ï‰-electrical method, simultaneously overcoming their main limitations, for example, a mandatory deposition of additional isolating and metal layers over the films and the previous knowledge of the thermal contact resistance between the heating and the mesoporous layers.